"A growth to understanding": An interview with Caryl Phillips about biographical fiction. (September 2020) - Ledent, Bénédicte; Phillips, Caryl; Tunca, Daria
Starting from the recognition of a biographical impulse in the work of Caryl Phillips, this interview focuses on his practice of biographical fiction. Among the issues raised are the increased popularity of life writing, the tension between fact and fiction at the heart of biographical narratives, the linguistic exactitude involved in focusing on historical characters, the role of research in the exploration of human lives, and the importance of emotional truth in novels that deal with famous individuals. This conversation sheds light on Phillips's specific approach to biofiction, particularly in his novels Dancing in the Dark (2005) and A View of the Empire at Sunset (2018), while also providing readers with a more general reflection on the genre in the postcolonial field.